DEVELOPMENT OF INFORMATION- COMPETENCE OF GEOGRAPHY TEACHERS ON THE BASIS OF AN INNOVATIVE APPROACH - Sarvinoz Baymuradova; Ural Safarov; Ziyoda Amanbayeva; Nurbol Karakulov (The Bioscan, 2024)
In this article, the development of information and communication competence of teachers, competences that make up competence, communicative ability, professional qualifications and skills, culture of information use, use of information and communication tools in geography lessons, innovative electronic programs, geoinformation system, "human + computer" relations, the integration of geography+ informatics sciences, the possibilities of using modern computer technologies in their professional activities are discussed.